Special Issue Feminist Legal Theory. - Austin Sarat (Studies in Law, Politics, and Society,, 2016)
Half a century after the beginning of the second wave, feminist legal theorists are still writing about many of the subjects they addressed early on: money, sex, reproduction, and jobs. What has changed is the way that they talk about these subjects. Specifically, these theorists now posit a more complex and nuanced conception of power. Recent scholarship recognizes the complexities of power in contemporary society, the ways in which these complexities entrench sex inequality, and the role that law can play in reducing inequality and increasing agency. The feminist legal theorists in this volume are emblematic of this effort. They carefully examine the relationship between gender, equality, and power across an array of realms: sex, reproduction, pleasure, work, money. In doing so they identify social, political, economic, developmental, and psychological and somatic forces, operating both internally and externally, that complicate the expression and constraint of power. Finally, they give sophisticated thought to the possibilities for legal interventions in light of these more complex notions of power.